Identification of SLAMF1 as an immune-related key gene associated with rheumatoid arthritis and verified in mice collagen-induced arthritis model - Li, Anqi; Zhang, Zhanfeng; Ru, Xiaochen; Yi, Yanfeng; Li, Xiaoyu; Qian, Jing; Wang, Jue; Yang, Xiaobing; Yao, Yunliang (Frontiers in Immunology, 2022)
Background: Rheumatoid arthritis (RA) is the most common inflammatory arthropathy. Immune dysregulation was implicated in the pathogenesis of RA. Thus, the aim of the research was to determine the immune related biomarkers in RA. Methods: We downloaded the gene expression data of RA in GSE89408 and GSE45291 from Gene Expression Omnibus public database (GEO). Differentially expressed genes (DEGs) were identified between RA and control groups. Infiltrating immune cells related genes were obtained by ssGSEA and weighted gene co-expression network analysis (WGCNA). We performed functional enrichment analysis of differentially expressed immunity-related genes (DEIRGs) by “clusterProfiler” R package, key genes screening by protein-protein interaction (PPI) network of DEIRGs. And mice collagen-induced arthritis (CIA) model was employed to verify these key genes. Results: A total of 1,885 up-regulated and 1,899 down-regulated DEGs were identified in RA samples. The ssGSEA analysis showed that the infiltration of 25 cells was significantly different. 603 immune related genes were obtained by WGCNA, and 270 DEIRGs were obtained by taking the intersection of DEGs and immune related genes. Enrichment analyses indicated that DEIRGs were associated with immunity related biological processes. 4 candidate biomarkers (CCR7, KLRK1, TIGIT and SLAMF1) were identified from the PPI network of DEIRGs and literature research. In mice CIA model, the immunohistochemical stain of joint tissue showed SLAMF1 has a significantly high expression in diseased joints. And flow cytometry analysis shows the expression of SLAMF1 on CIA mice-derived Th cells, γδT cells, CTL, NK cells, NKT cells, classical dendritic cell (cDCs) and monocytes/macrophages was also significantly higher than corresponding immune cells from HC mice Conclusion: Our study identified SMLAF1 as a key biomarker in the development and progression of RA, which might provide new insight for exploring the pathogenesis of RA.